The effects of cell-sizes, environmental conditions, and growth phases on the stregth of individual W303 yeast cells inside ESEM - Mohd. Ridzuan Ahmad, author; Masahiro Nakajima, author; Seiji Kojima, author; Michio Homma, author; Toshio Fukuda, author (2008)
PRZSL